Comprehensive investigation and risk study on pyrrolizidine alkaloid contamination in Chinese retail honey. (December 2020) - He, Yisheng; Zhu, Lin; Ma, Jiang; Wong, Lailai; Zhao, Zhongzhen; Ye, Yang; Fu, Peter P.; Lin, Ge
Abstract: Pyrrolizidine alkaloids (PAs) are common phytotoxins. We performed the first comprehensive investigation on PA contamination in Chinese honeys. LC-MS analysis revealed that 58% of 255 honey samples purchased from 17 regions across Mainland China and Taiwan contained PAs with total content ranging over 0.2–281.1 μg/kg. Monocrotaline (from Crotalaria spp), a PA never found in honey in other regions, together with echimidine ( Echium plantagineum ) and lycopsamine (from Senecio spp.), were three predominant PAs in PA-contaminated Chinese honeys. Further, PAs present in honeys were found to have geographically distinct pattern, indicating possible control of such contamination in future honey production. Moreover, we proposed a new risk estimation approach, which considered both content and toxic potency of individual PAs in honeys, and found that 12% of the PA-contaminated Chinese honeys tested might pose potential health risk. This study revealed a high prevalence and potential health risk of PA contamination in Chinese honeys. Graphical abstract: Image 1 Highlights: Over half (58%) of Chinese retail honeys tested are contaminated with PAs. Lycopsamine, echimidine, and monocrotaline are main PAs in Chinese honeys tested. Crotalaria spp., Senecio spp., and Echium plantagineum are the plant origins of PAs. PAs in Chinese honeys tested present geographically distinct patterns. About 12% of PA-contaminated Chinese honeys may pose potential health risk.